Konseling Kelompok Dengan Teknik Motivational Interviewing Untuk Meningkatkan Kepercayaan Diri Pada Korban Bullying Di Desa Talang Cempedak - Anisa Putri; Suryati Suryati; Hartika Utami Fitri (Journal on Education, 2025)
The study entitled "Group Counseling with Motivational Interviewing Technique to Increase Self-Confidence in Bullying Victims in Talang Cempedak Village" has a background, namely teenagers who experience bullying behavior and have low self-confidence. So that the attitudes shown include the victims are often silent, do not interact with their peers, often feel worthless and incapable, show doubtful attitudes and avoid eye contact. This study aims to determine the level of self-confidence of bullying victims before and after receiving group counseling with the Motivational Interviewing technique and how effective group counseling with the Motivational Interviewing technique is in increasing the self-confidence of bullying victims. This study uses a quantitative approach with an experimental research type. The population in this study amounted to 30 bullying victims. The sampling technique used Purposive Sampling which was selected based on criteria totaling 15 people. The data analysis technique used the Wilcoxon test. The results of this study indicate that the self-confidence of bullying victims has increased and is in the moderate category. Which shows that the results of the Wilcoxon test found the Asymp.sig value (2-tailed) between the two groups were 0.012 and 0.016 where 0.012 and 0.016 <0.05. Therefore, Ha is accepted and Ho is rejected. The results show that group counseling can increase self-confidence in bullying victims in Talang Cempedak Village.